Pengaruh Volume Perdagangan, Kurs Dan Risiko Pasar Terhadap Return Saham Pada Perusahaan Lq-45 Di Bursa Efek Indonesia Tahun 2018-2020 - Bernike Bilha Damaris Mardiyanto; Rr Tjahjaning Poerwati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to prove the effect of trading volume, exchange rate, and market risk on stock returns of LQ-45 companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The type of research conducted is causal associative research. The research population includes LQ-45 companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period as many as 36 companies. The sampling technique used purposive sampling in order to obtain 108 samples. The data analysis method used is multiple linear regression. Based on the results of the research, trading volume has a positive and significant effect on stock returns, as evidenced by the beta coefficient value of  at a significance value of 0.006. Exchange rate does not affect the return of shares is evidenced by the value of the beta coefficient of  the significant value of 0.072. Market risk has a positive and significant effect on stock returns as evidenced by the beta coefficient value of 0.041 at a significance value of 0.000. The multiple linear regression equation in this study is Y = (-1.484) +  Volume +  Exchange Rate + 0.041 Beta + e